Full-Length Transcriptome Sequencing of Pinus massoniana Under Simulated Monochamus alternatus Feeding Highlights bHLH Transcription Factor Involved in Defense Response - Quanmin Wen; Yajie Cui; Tian Xu; Yadi Deng; Dejun Hao; Ruixu Chen (Plants)
Background: Pinus massoniana is a significant lipid-producing tree species in China and a susceptible host for both the pine wood nematode and its insect vector, Monochamus alternatus. The basic helix–loop–helix (bHLH) family of transcription factors play a crucial role in responding to both biotic and abiotic stresses. However, the role of bHLH in terpene-induced defense in P. massoniana remains poorly studied. Results: Transcriptome sequencing using DNA Nanoball Sequencing (DNBSEQ) and PacBio Sequel platforms was performed, revealing differences in gene expression in P. massoniana branch under the simulated feeding treatment of methyl jasmonate (MeJA) spraying. Fifteen bHLH genes were cloned and analyzed, among which eight highly upregulated PmbHLH genes showed similar temporal expression after MeJA treatment and M. alternatus adult feeding. Five highly upregulated bHLH genes with nuclear localization were highly expressed in P. massoniana after M. alternatus feeding and interacted with the promoter of the terpene synthase gene Pm TPS (−)-α-pinene, confirming their involvement in the defense response of P. massoniana against the M. alternatus adult feeding. Conclusions: Our results unveil the temporal changes and the regulation of the induced defense system in P. massoniana mediated by both MeJA signaling and M. alternatus feeding treatment. The potential application for transgenic experiments and the breeding of resistant species in the future were discussed.